Amifostine-loaded armored dissolving microneedles for long-term prevention of ionizing radiation-induced injury. (August 2020) - Yu, Xiang; Li, Minshu; Zhu, Lin; Li, Jingfei; Zhang, Guoli; Fang, Rongzhen; Wu, Zhihong; Jin, Yiguang
Abstract: Amifostine is a cytoprotective agent against the hematopoietic damage induced by ionizing radiation, although the intravenous injection of amifostine is a unique administration method with strict dosing time limitation. Hence, the fields of application of amifostine are greatly limited. Here, we developed an amifostine-loaded armored microneedle (AAMN) with long-term prevention of hematopoietic injury induced by ionizing radiation. First, amifostine-loaded hyaluronic acid microneedles (AMNs) were fabricated, and the AMNs were then dipped in an N-vinyl-2-pyrrolidone (NVP) solution followed by ultraviolet (UV) photocuring to obtain AAMNs. AAMNs were nail-shaped with much higher mechanical strength compared to the conical shape and weak strength of AMNs, which was verified by their in silico simulation. In the in vitro release experiment, more than 55% of amifostine was released from AAMNs within 10 min, and 95% was released in 60 min. Drug skin permeation of AAMNs was also high, at twice that of AMNs. AAMNs provided long-term protection of the hematopoietic system from radiation within 3−7 h pre-radiation compared to the unique amifostine injection 0.5 h pre-radiation because topical application of AAMNs led to the long-term maintenance of the in vivo effective drug concentration. More importantly, AAMNs led to the survival of all irradiated mice due to intravenous amifostine. AAMNs are a promising transdermal delivery system of amifostine for long-term protection against ionizing radiation-induced injury. Statement of Significance: An amifostine-loaded dissolving armored microneedle (AAMN) patch is developed for long-term prevention of ionizing radiation-induced injury. High drug loads in microneedles (MNs) with adequate mechanical strength is a challenge. We fabricated armors on the surface of high amifostine-loaded hyaluronic acid microneedles (AMNs) by dipping the tips of AMNs in N-vinyl-2-pyrrolidone (NVP) solutions and then subjecting them to UV irradiation, and high-strength armored AMNs (AAMNs) were obtained. AAMNs show deeper skin insertion and much higher drug permeation than AMNs. The controlled drug release from AAMNs in the mouse skins provides a long-term protection of radiation-induced injury with 3−7 h administration pre-radiation compared to the merely 0.5-h point of amifostine injection. Graphical abstract: Image, graphical abstract